2011
DOI: 10.1017/s1461145711001453
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Rgs2 gene expression level and anxiety and depression-like behaviour in a mutant mouse model: serotonergic involvement

Abstract: RGS2 is a member of a family of proteins that negatively modulate G-protein coupled receptor transmission. Variations in the RGS2 gene were found to be associated in humans with anxious and depressive phenotypes. We sought to study the relationship of Rgs2 expression level to depression and anxiety-like behavioural features, sociability and brain 5-HT1A and 5-HT1B receptor expression. We studied male mice carrying a mutation that causes lower Rgs2 gene expression, employing mice heterozygous (Het) or homozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 52 publications
3
46
0
3
Order By: Relevance
“…Even though no mechanisms were elucidated in how RGS2 might control the various responses in organs, the knockout mice provided a foundation for understanding the physiological functions of RGS2 (Tuomi et al, 2010). Recent genetic quantitative trait analysis has shown that RGS2 is a gene that controls anxiety in mice and possibly humans (Hettema et al, 2013;Le-Niculescu et al, 2011;Lifschytz et al, 2012;Mouri et al, 2010;Muinos-Gimeno et al, 2011;Okimoto et al, 2012;Otowa et al, 2011;Stein et al, 2014;Yalcin et al, 2004).…”
Section: Rgs2mentioning
confidence: 99%
“…Even though no mechanisms were elucidated in how RGS2 might control the various responses in organs, the knockout mice provided a foundation for understanding the physiological functions of RGS2 (Tuomi et al, 2010). Recent genetic quantitative trait analysis has shown that RGS2 is a gene that controls anxiety in mice and possibly humans (Hettema et al, 2013;Le-Niculescu et al, 2011;Lifschytz et al, 2012;Mouri et al, 2010;Muinos-Gimeno et al, 2011;Okimoto et al, 2012;Otowa et al, 2011;Stein et al, 2014;Yalcin et al, 2004).…”
Section: Rgs2mentioning
confidence: 99%
“…Deletion of rgs2 in mice produces increased anxiety-related behavior (Lifschytz et al, 2012;Oliveira-Dos-Santos et al, 2000;Yalcin et al, 2004) and avoidance behavior in novel social situations (Lifschytz et al, 2012). Mice lacking rgs2 have also been reported to show reduced expression of 5HT 1a G protein-coupled presynaptic autoreceptors (thought to be involved in the therapeutic activity of SSRIs) in the raphe (Lifschytz et al, 2012). Of note, the G allele of rs4606, which we found to predict reduced sertraline response, has been associated with reduced expression of RGS2 (Semplicini et al, 2006).…”
Section: Discussionmentioning
confidence: 63%
“…Among other functions, RGS2 accelerates the deactivation of G proteins to reduce neuronal G protein-coupled receptor response to neurotransmitters including serotonin (Kimple et al, 2011). Deletion of rgs2 in mice produces increased anxiety-related behavior (Lifschytz et al, 2012;Oliveira-Dos-Santos et al, 2000;Yalcin et al, 2004) and avoidance behavior in novel social situations (Lifschytz et al, 2012). Mice lacking rgs2 have also been reported to show reduced expression of 5HT 1a G protein-coupled presynaptic autoreceptors (thought to be involved in the therapeutic activity of SSRIs) in the raphe (Lifschytz et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have shown a role for this RGS protein in modulating anxiety, with polymorphisms in RGS2 associated with generalized anxiety disorder (Smoller et al, 2008;Koenen et al, 2009;Hohoff et al, 2015), panic disorder Otowa et al, 2011;Hohoff et al, 2015), post-traumatic stress disorder , as well as suicide (Cui et al, 2008) in humans. Studies in mice have also shown an association between RGS2 and anxiety (Oliveira-Dos-Santos et al, 2000;Yalcin et al, 2004;Lifschytz et al, 2012;Okimoto et al, 2012) with decreased RGS2 expression causing anxiety (Oliveira-Dos-Santos et al, 2000;Lifschytz et al, 2012) and depression-like (Lifschytz et al, 2012) phenotypes. To better treat these diseases associated with RGS2, it is necessary to understand how RGS2 modulates synaptic plasticity and signaling.…”
Section: Rgs2mentioning
confidence: 99%
“…Ga q at the RGS domain (Heximer et al, 1997;Ingi et al, 1998) Hippocampus (Han et al, 2006) Presynaptic in hippocampal pyramidal neurons (Han et al, 2006) Regulates short-term synaptic plasticity in the hippocampus (Han et al, 2006) Anxiety (Doupnik et al, 1997;Lifschytz et al, 2012;Okimoto et al, 2012;Hohoff et al, 2015) Ga i/o at the RGS domain (Ingi et al, 1998;Han et al, 2006) Striatum (Labouèbe et al, 2007) Postsynaptic in dopamine neurons in the VTA (Labouèbe et al, 2007) Disinhibits GABA-mediated inhibition of dopamine neurons in the VTA (Labouèbe et al, 2007) Depression (Lifschytz et al, 2012;Mandelli and Serretti, 2013) Amygdala (Okimoto et al, 2012) NA (Not available)…”
Section: Rgs2mentioning
confidence: 99%